A study of copper diffusion through Pd₂Si thin films - Geduld, Dieter Rudi (Department of Physics, 2016)
It is now generally recognized that unless an alternative for aluminium is found the resistivity of the metal interconnects will soon limit device performance. Copper, with its low resistivity and greater resistance to electromigration is one of the obvious substitutes. However, before aluminium can be replaced by copper, a careful study of the reactivity of copper with metal-silicides used in devices needs to be carried out. This study involves a dynamic RBS investigation of the reaction of copper with Pd₂Si films grown on Si<100> and Si<lll> substrates. It was found that copper diffused through the Pd₂Si layer and reacted with the single crystal silicon substrate at relatively low temperatures. The onset temperature observed for copper diffusion was found to differ for Pd2Si films grown on the two different substrate orientations, Si<100> and Si<lll>. Measurements of the activation energies for Cu-silicide growth on Pd₂Si/Si<100> and Pd₂Si/Si<lll> were also made.